Libya-United States Relations, 1969-1986 - M. Assllami, Masaud Almahdi (1999)
This thesis examines Libya-United States Relations from 1969 until 1986. The period between the September 1969 Revolution and 1986 saw an important development in the relationship between the two countries. The September Revolution marked a shift in the pattern of Libya-United States relations as Libya took a more independent approach to conducting its domestic affairs and establishing foreign relations not only with the United States, but with other countries as well. It was this shift in Libyan domestic and foreign policies that set a new trend in its relations with the United States. This study was based on a historical approach and the re-examination of secondary documents such as books, newspaper clippings, official publications and my own experience as a foreign affairs officer. The study discovered several important developments and factors that shaped Libya-United States Relation between 1969-1986. Firstly, relations between Libya and the United States deteriorated especially after the September 1969 Revolution when the leadership of the former passed over to Colonel Muammar Qadhafi, a military personnel, who brought in his personal style of leadership that was backed by popular Libyan support. Qadhafi's attempt to construct a new and truly independent Libya and make the country a key international player in the region were strongly met with resistance, especially from the United States which had grown use to its increasingly dominant role in the region and which had also gone unchallenged. Secondly, Libya' s firm stand on its national independence and its actions to remove foreign influences and domination triggered the start of a sour relation with the United States. This turn of relation was not augmented by the fact that Libya was also a strong proponent of the Arab nationalism and its undivided support for pan-African nationalism. As Libya's began to take a more dominant role in the region, the country was becoming increasingly viewed in negative light. United States' perception of Libya was beginning to be couched in terms such as "terrorists" or "sponsors" of terrorism on the international scale. Thirdly, the deterioration in the bilateral relations between the two countries was manifested by the trade volumes that plummeted especially in the post- 1 969 period. Before this period, relations between the two had been marked by friendly relations and was demonstrated by the presence of not only the American military personnel but also of a sizeable American business community, especially in Tripoli. Fourthly, the deteriorating relations between the two countries were attributed to several factors such as the American perception of Libya as a state that supported terrorists and terrorist acts and Libya's negative image that was being perpetrated by the western media and prominent personalities that were close to the American leadership. Lastly, this study ended in 1986 because this period represented the lowest ebb in Libya-United States relations. By this period, there was no formal relation as both countries withdrew diplomatic representations in each other's capital. Signs of better relations only seem to have resurfaced in the late 1990s. However, the extent to which this might develop further to benefit the peoples of the two countries remains to be seen. But this contemporary development in the Libya-United States relations is not within the scope of this study.